A nők és a földkérdés a Kelet-afrikai Közösség tagállamaiban - Bagi, Judit (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
In this paper I am introducing the change in women’s rights regarding land inheritance and the way it has impacted society in the member states of the East African Community. Besides presenting the results achieved, I am highlighting its inadequacies and the challenges yet to solve as well. Some interviews have aided my research, which I have conducted recently about the East African land inheritance situation with international Africa experts, and with the representative of the Rwandan Gender Monitoring Office in 2016. I am focusing on Rwanda, but also mentioning Kenya, Uganda, Burundi, Tanzania, and South Sudan due to the regional comparison of the relevant laws affecting land ownership and inheritance.